Multi-Residue Method for the Analysis of Stilbene Estrogens in Milk - Guan, Tianzhu (Int J Mol Sci, 2019)
The rapid analysis of stilbene estrogens is crucially important in the environment, food and health sectors, but quantitation of lower detection limit for stilbene estrogens persists as a severe challenge. We herein described a homologous and sensitive fluorescence polarization (FP) assay based on estrogen receptor α ligand binding domain (ER-LBD) to monitor stilbene estrogens in milk. Under optimal conditions, the half maximal inhibitory concentrations (IC(50)) of the FP assay were 9.27 nM, 12.94 nM, and 22.38 nM for hexestrol, dienestrol and diethylstilbestrol, respectively. And the corresponding limits of detection (LOD) values were 2.94 nM, 2.89 nM, and 3.12 nM. Finally, the assay was applied to determine the stilbenes in milk samples where the mean recoveries ranged from 95.76% to 112.78% and the coefficients of variation (CV) below 12.00%. Furtherly, we have focused our study on high cross-reactivity phenomena by using two in silico approaches, including molecular docking analysis and topology analysis. Overall, docking results show that several residues in the hydrophobic pocket produce hydrophobic interactions with the tested drug molecules, which contribute to the stability of their binding. In this paper, we conclude that the FP method is suitable for the rapid detection of stilbenes in milk samples, requiring no expensive analytical equipment or time-consuming sample preparation. This work offers a practical approach that applies bioscience technology in food safety testing and improves analytical speed and laboratory efficiency.